MANAJEMEN MUTU SEKOLAH DAN MADRASAH - Edy Muslimin (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
The quality of national education has declined, further away from the ideals officially proclaimed by the founding fathers. In addition, the complexity of the problems addressed in the quality of schools or madrasas, especially religious leaders and teachers as educators. Another phenomenon that can be observed is the National Education Law no. 2 of 1989 was unable to face global challenges and domestic challenges. The results showed that management is a tool to achieve a goal, good management facilitates achieving the goals of an institution. The quality targets of schools and madrasas include inputs, processes and outputs. The quality assurance system is in the form of school and Madras quality standards through internal and external quality audits. Steps in quality assurance according to Deming through the plan (plan), do (organize), check (monitoring) and action (implementation).